ROLE OF SALIVARY BIOMARKERS IN EARLY DETECTION OF ORAL CANCER – INVESTIGATING HOW SPECIFIC BIOMARKERS IN SALIVA CAN BE USED FOR EARLY DIAGNOSIS AND PROGNOSIS OF ORAL SQUAMOUS CELL CARCINOMA - Dr. Tariq Ahmad Lone; Dr. Arezoo Bashir Peerzada; Dr. Arman Bashir Peerzadah; Dr. Roohie Khanam (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background: Oral squamous cell carcinoma (OSCC) is among the most common malignancies, particularly in regions with high tobacco and betel nut consumption. Delayed diagnosis contributes to poor prognosis and high mortality rates. Traditional diagnostic methods are invasive, costly, and time-consuming. Salivary biomarkers offer a promising non-invasive alternative for early detection and prognosis, potentially improving patient outcomes. Aim: This study evaluates the diagnostic potential of salivary biomarkers, including IL-6, IL-8, VEGF, miRNA-21, and MMP-9, in detecting OSCC at an early stage and assessing disease progression. Methods: A prospective study was conducted at Government Dental College, Srinagar, over a period of 24 months (July 2022 – July 2024). Saliva samples were collected from 60 patients diagnosed with OSCC and 60 healthy controls. Biomarker levels were analyzed using ELISA for cytokines and growth factors, RT-PCR for microRNA detection, and mass spectrometry for protein profiling. Sensitivity, specificity, and predictive values were calculated using statistical analysis. Results: Significant differences were observed between OSCC patients and controls. IL-6 and IL-8 levels were elevated by 3.8-fold and 4.2-fold, respectively (p < 0.001), while VEGF and miRNA-21 showed a 2.7-fold and 3.1-fold increase (p < 0.05). MMP-9 levels were also significantly higher in advanced-stage OSCC patients. ROC curve analysis demonstrated high diagnostic accuracy, with IL-8 showing the highest sensitivity (91%) and specificity (89%) in distinguishing OSCC from healthy individuals. Conclusion: Salivary biomarkers, particularly IL-6, IL-8, VEGF, miRNA-21, and MMP-9, show strong potential for early OSCC detection and prognostic assessment. Their integration into clinical practice could reduce reliance on invasive biopsy procedures and improve early diagnosis rates. Further large-scale studies are needed to standardize biomarker panels and establish reference values.